1998
DOI: 10.1084/jem.187.6.961
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β1, in the Presence of Granulocyte/Macrophage Colony-stimulating Factor and Interleukin 4, Induces Differentiation of Human Peripheral Blood Monocytes into Dendritic Langerhans Cells

Abstract: Langerhans cells (LCs) are dendritic cells (DCs) that are present in the epidermis, bronchi, and mucosae. Although LCs originate in bone marrow, little is known about their lineage of origin. In this study, we demonstrate that in vitro LCs may originate from monocytes. Adult peripheral blood CD14+ monocytes differentiate into LCs (CD1a+, E-cadherin+, cutaneous lymphocyte-associated antigen+, Birbeck granules+, Lag+) in the presence of granulocyte/macrophage colony-stimulating factor, interleukin 4, and transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
383
2
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(416 citation statements)
references
References 22 publications
26
383
2
5
Order By: Relevance
“…Human monocytes were magnetically isolated from PBMCs by depletion (monocyte isolation kit II, Miltenyi Biotec). MoDC and MoLC were generated from same donor blood in RPMI 1640 supplemented with 2 mM L-glutamine, 100 IU/mL penicillin, 100 mg/mL streptomycin, and 10% v/v heat-inactivated FBS (Biochrom) by 6-day culture with human recombinant GM-CSF (100 ng/mL), IL-4 (10 ng/mL [32]), and TGF-b1 (for MoLC only, 10 ng/mL, R&D Systems, Wiesbaden-Nordenstadt, Germany [22]). Then CD1c 1 cells were positively selected by CD1c-MACS as described above for epidermal LC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human monocytes were magnetically isolated from PBMCs by depletion (monocyte isolation kit II, Miltenyi Biotec). MoDC and MoLC were generated from same donor blood in RPMI 1640 supplemented with 2 mM L-glutamine, 100 IU/mL penicillin, 100 mg/mL streptomycin, and 10% v/v heat-inactivated FBS (Biochrom) by 6-day culture with human recombinant GM-CSF (100 ng/mL), IL-4 (10 ng/mL [32]), and TGF-b1 (for MoLC only, 10 ng/mL, R&D Systems, Wiesbaden-Nordenstadt, Germany [22]). Then CD1c 1 cells were positively selected by CD1c-MACS as described above for epidermal LC.…”
Section: Methodsmentioning
confidence: 99%
“…TGF-b is required for differentiation and survival of LC and is produced in an autocrine or paracrine way [20,21]. We have recently shown that epidermal LC express TLR2 protein for TLR2 and reported that agonists could activate the NFkB pathway, induce cell migration and IL-6 expression in monocyte-derived LC-like cells (MoLC [22,23]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it has already been established that CD68þ/factor XIIIaþ dendritic cells and TGFb1 orchestrate the host response to eliminate noxious putative etiologic agents, it is likely that these factors have this role in NSF (20). The high levels of TGFb1 expression and its role in the regulation of dendritic cell maturation (22,23) suggest at least one mechanism that may promote lesion formation in NSF (20).…”
Section: Monocytes and Macrophages In Nsfmentioning
confidence: 99%
“…CSF has been reported to contain GM-CSF, a key growth factor for myeloid DC [15]. TGF-b, which is constitutively present in the CSF and mediates the ability of CSF to suppress the DTHinducing potential of macrophages [16], can divert myeloid DC development towards Langerhans-like cells [17,18] and prevent LPS-or TNF-induced DC maturation [19]. On the other hand, vasoactive intestinal peptide constitutively present in CSF [20] can induce DC maturation and potentiate maturation induced by TNF-a [21].…”
Section: Introductionmentioning
confidence: 99%